Response of yearling steers to burning and fertilizing bluestem pasture and intensively stocking early - Smith, E.F.; Harbers, L.H.; Owensby, Clenton E.; Boggs, Don (Kansas State University. Agricultural Experiment Station, 2011)
Six pastures totaling 328 acres were summer grazed by yearling steers. Four pastures were burned April 23, 1976; two were not burned. One of the burned pastures had 40 lbs. of nitrogen per acre applied aerially April 29, 1976. Another burned pasture was stocked at twice the normal rate (intensively stocked early) from April 28 to July 15. The other pastures were stocked from April 28 to October 6, 1976.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Steers; Bluestem